2014
DOI: 10.1111/jcpt.12186
|View full text |Cite
|
Sign up to set email alerts
|

Is a flavonoid-rich diet with steamer cooking safe during calcineurin inhibitors therapy?

Abstract: Summary What is known and objective Dietary therapy is recommended for decreasing the symptoms of the metabolic syndrome and the risk of type 2 diabetes and cardiovascular diseases in subjects on calcineurin inhibitors. However, food–drug interactions may occur particularly with patients on such immunosuppressive therapy. This article comments on the benefit/risk assessment of a flavonoid‐rich diet and steam‐cooking of such food during calcineurin inhibitors therapy. Comment Patients are commonly advised again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the last few years, several studies, both in vitro and in vivo, have focused on the effects of Brassicaceae on chronic diseases and on the bioactive compounds of these plants that may be responsible for the observed effects [ 7 , 8 ] ( Figure 1 ). It has been discussed that the known healthy effects of Brassicaceae may be related to the presence of several bioactive compounds in the edible parts, such as ascorbic acid (AsA), phenolics, carotenoids, and glucosinolates, as summarized in Table 1 [ 9 , 10 ].…”
Section: Bioactive Compounds In Brassicaceae Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, several studies, both in vitro and in vivo, have focused on the effects of Brassicaceae on chronic diseases and on the bioactive compounds of these plants that may be responsible for the observed effects [ 7 , 8 ] ( Figure 1 ). It has been discussed that the known healthy effects of Brassicaceae may be related to the presence of several bioactive compounds in the edible parts, such as ascorbic acid (AsA), phenolics, carotenoids, and glucosinolates, as summarized in Table 1 [ 9 , 10 ].…”
Section: Bioactive Compounds In Brassicaceae Anmentioning
confidence: 99%
“…Adverse effects of compounds that are present in Brassicaceae towards metabolic syndromes are also possible. For example, the potential additive and synergistic effects of flavonoids from Brassicaceae with other molecules could interfere with the bioavailability of specific drugs with a narrow therapeutic index [ 9 ].…”
Section: Bioactive Compounds In Brassicaceae Anmentioning
confidence: 99%
“…Cruciferous vegetables have been considered sanatory, and can reduce the risk of chronic diseases (Raiola et al, 2017). The bioactive compounds that have been reported are ascorbic acid, phenolics, carotenoids, and glucosinolates (Peluso and Palmery, 2014). Sulforaphane, also known as isothiocyanate 1-isothiocyanato-(4R)-(methylsulfinyl) butane (Figure 1A), is a kind of isothiocyanate that is a hydrolysate of glucosinolates produced by the enzyme myrosinase in cruciferous vegetables (Raiola et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[14]. Levels of flavanols comparable to those of formulated supplements can be reached with 180 g of apples or 8 g of dark chocolate, and a serving of 150-200 g of red fruits may yield amounts of flavanols and anthocyanins that are comparable to those of formulated supplements [15]. The EFSA Panel concluded that there is evidence from interventional clinical trials that the intake of doses equal to or above 800 mg epigallocatechin gallate (EGCG)/day taken as a food supplement has been shown to induce a statistically significant increase of serum transaminases in treated subjects compared to control [16].…”
mentioning
confidence: 99%